Derailed Values: Planning Education, External Funding, and Environmental Justice in New Orleans Rail Planning. (December 2018) - Lowe, Kate; Ehrenfeucht, Renia
Studio courses can transform practice and impart planning values, but increasing university expectations around revenue generation could create barriers for these objectives. To understand how funding demands could impact planning education, we examine a New Orleans–based case study in which external funders pressured university stakeholders to change a studio course. The studio, focused on environmental justice and freight rail planning, remained much the same, but shifted from an advocacy framework to a technical approach. This approach did little to impart social justice values or transform practice, but planning education can still support social justice values.